Paraneoplastic Fever, Leukemoid Reaction and Thrombocytosis in Transitional Cell Carcinoma of Kidney: A Rare Presentation - Yadav, Rajiv; Chaudhary, Suchet; Yadav, Poonam; Kumar, Abhay (Indian Journal of Case Reports, 2016)
We report a rare presentation of transitional cell carcinoma of kidney with paraneoplastic fever, leukemoid reaction and thrombocytosis. Description of the case highlights an unusual clinical scenario where fever, leucocytosis, pyuria and raised procalcitonin levels at presentation in a patient with transitional cell carcinoma of kidney may mislead diagnostic work up toward an infective cause (i.e. pyelonephritis). This case will guide clinician to keep a high index of suspicion, in case they encounter such a situation.